Perioperative Management of a Patient with Hereditary Angioedema and Intestinal Obstruction Secondary to an Ileal Tumor: A Case Report - Antony Peter Gatheru; Anne Kasyoka Barasa; Isaac Karogo Mwangi; Stanley Ngare; Dan Kiptoon; Edwin Oloo Walong (The Annals of African Surgery)
Hereditary angioedema (HAE) is a rare genetic disorder resulting from deficiency or dysfunction of the C1-esterase inhibitor (C1-INH, C1-inhibitor) protein. It manifests with recurrent cutaneous and submucosal edema involving the extremities, abdomen, and/or larynx. Abdominal edema mimics other acute abdominal conditions including intestinal obstruction, potentially prompting unnecessary surgery if misdiagnosed. Prompt treatment with C1-INH typically alleviates abdominal angioedema symptoms within 24 hours, while untreated cases resolve within 2–5 days. Persistence of abdominal symptoms warrants further evaluation for other etiologies of acute abdomen. Surgical procedures with tracheal intubation can induce life-threatening upper airway edema in HAE patients. We describe the successful management of a 41-year-old female with HAE presenting with features of intestinal obstruction, which only partially resolved with the administration of C1-INH and conservative bowel decompressive management. Imaging revealed a small bowel tumor necessitating surgical intervention. Pre-operative prophylactic C1-INH was administered, followed by open laparotomy under general anesthesia with endotracheal intubation. Although C1-INH concentrates are the principal treatment for abdominal HAE attacks, other causes of acute abdomen should be considered, particularly in cases of persistent symptoms, to guide appropriate management. This case highlights the importance of multidisciplinary collaboration and careful perioperative planning to optimize outcomes for HAE patients requiring surgery.